2007
DOI: 10.1101/pdb.prot4893
|View full text |Cite
|
Sign up to set email alerts
|

Fate-Mapping Technique: Targeted Whole-Embryo Electroporation of DNA Constructs into the Germ Layers of Mouse Embryos 7-7.5 Days Post-coitum

Abstract: INTRODUCTIONFate maps reveal body plan organization and presage the expression of molecular characteristics of cell lineages and formation of body parts. This protocol targets DNA expression constructs into the germ layers of gastrula-stage mouse embryos by focal electroporation. Plasmids utilizing a promoter that drives widespread, non-lineage-restricted expression of transgenes are introduced to cells in defined germ layer regions by whole-embryo electroporation. Germ-layer cells are exposed to the DNA by mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 2 publications
2
11
0
Order By: Relevance
“…Consistent with a previous study 11 , GFP + cells were detected in embryos 1-2 hr after electroporation ( Figure 2E and 2G). When distal epiblast cells at the late primitive streak stage embryo were electroporated, labelled cells contributed to the neural ectoderm after 24 hr in culture ( Figure 2E and 2F).…”
Section: Electroporationsupporting
confidence: 80%
See 2 more Smart Citations
“…Consistent with a previous study 11 , GFP + cells were detected in embryos 1-2 hr after electroporation ( Figure 2E and 2G). When distal epiblast cells at the late primitive streak stage embryo were electroporated, labelled cells contributed to the neural ectoderm after 24 hr in culture ( Figure 2E and 2F).…”
Section: Electroporationsupporting
confidence: 80%
“…For electroporation of nucleic acids in embryonic tissues, gold plated electrodes have most commonly been used, allowing targeting of cells in a broad spatial range [7][8][9] . To achieve a more localized gene transfer, a needle-shaped electrode has been utilized to achieve a focal electric field 10,11 . Using this method, the authors showed that after the electroporation, around 30-60 cells had taken up the DNA construct 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescent protein expression was detected in one to four VE cells 4 h after plasmid electroporation (Fig. 4D, n=14), a timing in agreement with previous observations (Davidson et al, 2003;Khoo et al, 2007). Prominent apical vacuoles and basal projections in migrating DVE cells were observed when cytoplasmic or membranetargeted fluorescent proteins were used ( Fig.…”
Section: Dielectric Guide-based Devices Allow Reproducible Localised supporting
confidence: 78%
“…This limitation has been overcome by replacing one of the plates by a needle (Fig. 1C), thereby creating a significant variation of the electric potential over a small area (Davidson et al, 2003;Khoo et al, 2007). Importantly, permeation is efficiently restricted in space only if the needle is close enough to the targeted tissue, which may result in cell damage.…”
Section: Resultsmentioning
confidence: 99%